EFEKTIVITAS TEKNIK REINFORCEMENT POSITIF DALAM KONSELING INDIVIDU UNTUK MENINGKATKAN MOTIVASI BELAJAR SMA NEGERI 1 SANGKAPURA - Ainun Nazhirah; Ayomg Lianawati (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of the study was to determine the effectiveness of positive reinforcement techniques for learning motivation at SMA Negeri 1 Sangkapura. This study uses a quantitative approach with a single-subject method (single-subject design). In this study, students of classes XI-Mia 3 and 4 were used as an experimental sample, amounting to 2 students using the purposive sampling technique to get the results that they have low learning motivation potential. This research method uses a learning motivation questionnaire. The data analysis technique used descriptive statistics. The results showed that individual counseling services were given using positive reinforcement techniques for student learning. Effectively the two counselees have different results, counselee 1 overlap which is generated 0% while the second counselee 20%. Individual counseling services with positive reinforcement techniques can increase student learning motivation with the support of the results of data analysis.